Physical Activity and Its Effects on Cancer Prevention, Survival Rates, and Recovery - Michalina Dubińska; Wiktoria Paduch-Jakubczyk; Wiktoria Bilska; Urszula Ciułek; Anna Dobosz; Wiktoria Zduńczyk (Nicolaus Copernicus University in Toruń, 2024)
Introduction and Objective: Physical activity is any movement using skeletal muscles. It can be classified into four main categories: occupational, household, transport and recreational. These activities can also vary in intensity. This article aims to describe how physical activity affects cancer prevention, survival rates and recovery. Review and Methods: Review and summary of studies and meta-analysis of studies available in open-source format on Google Scholar and PubMed. State of Knowledge: Extensive research shows that regular physical activity reduces the risk of several cancers, particularly breast, colon, and endometrial cancers. Epidemiological studies consistently find that more active individuals have a lower incidence of certain cancers. Physical activity is also a useful adjunct to treatment, alleviating its negative effects. The protective effect of physical activity is believed to be dose-dependent, with greater benefits from higher frequencies, durations, and intensities. Recent studies suggest that physical activity may also improve survival rates in cancer patients, particularly for prostate, colorectal, and breast cancers. Conclusions: The current data strongly supports the inclusion of regular physical activity as a key component of cancer prevention strategies. It may also be beneficial for cancer patients to enhance their chances of survival. Public health guidelines stress the importance of exercise to lower cancer risk and improve overall health.